2021
DOI: 10.3389/fcimb.2021.681588
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Multidrug-Resistant Escherichia coli Producing CTX-M, MCR-1, and FosA in Retail Food From Egypt

Abstract: In this study, multidrug-resistant (MDR) Escherichia coli isolates from retail food and humans assigned into similar Multilocus Sequence Types (MLST) were analyzed using whole genome sequencing (WGS). In silico analysis of assembled sequences revealed the existence of multiple resistance genes among the examined E. coli isolates. Of the six CTX-M-producing isolates from retail food, blaCTX-M-14 was the prevalent variant identified (83.3%, 5/6). Two plasmid-mediated fosfomycin resistance genes, fosA3, and fosA4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Colistin-resistant E. coli isolates exhibited resistance to cephalothin, cefazolin, ceftazidime, ampicillin, amoxicillinclavulanic acid, cefoxitin, cefotaxime, piperacillin-tazobactam, and fosfomycin. Concurrently, nearly similar patterns were obtained recently for E. coli against several antibiotics in India, Croatia, and Egypt (Zdolec et al, 2016;Singh et al, 2018;Ramadan et al, 2021;Soliman et al, 2021). For K. pneumoniae isolates, the antibiotic resistance pattern was closely like the pattern of Brazilian MDR K. pneumoniae isolates (Ferreira et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Colistin-resistant E. coli isolates exhibited resistance to cephalothin, cefazolin, ceftazidime, ampicillin, amoxicillinclavulanic acid, cefoxitin, cefotaxime, piperacillin-tazobactam, and fosfomycin. Concurrently, nearly similar patterns were obtained recently for E. coli against several antibiotics in India, Croatia, and Egypt (Zdolec et al, 2016;Singh et al, 2018;Ramadan et al, 2021;Soliman et al, 2021). For K. pneumoniae isolates, the antibiotic resistance pattern was closely like the pattern of Brazilian MDR K. pneumoniae isolates (Ferreira et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…A previous study has identified mcr-1 gene in one E. coli isolate from a cow suffering from subclinical mastitis in Egypt (Khalifa et al, 2016). Although the mcr-1 gene was detected frequently from different samples (Khalifa et al, 2016;Lima Barbieri et al, 2017;Ramadan et al, 2021), it is foremost found here in the raw milk samples. Marvelously, one E. coli isolate carrying mcr-1 gene obtained from hard cheese made from raw milk was reported in Egypt very lately (Ombarak et al, 2021), which in turn lightens the importance of raw milk quality control checks in Egypt, focusing on farm workers as well as the animal itself.…”
Section: Discussionmentioning
confidence: 72%
“…In our previous analysis, the odds of being a high user of antimicrobials in turkeys were significantly higher for those that used any antimicrobial via water and those that used folate pathway inhibitors, bacitracin, and tetracyclines. These findings highlight the potential role of co-selection for resistance or selection for fitness of specific AMR strains and could be explained by the co-location and transmission of antimicrobial resistance genes on mobile genetic elements (e.g., plasmids or integrons) (Johnson et al, 2012;Sheikh et al, 2012;Ahmed et al, 2013;Cazer et al, 2019;Ramadan et al, 2021). Another potential explanation is that the long-term use of antimicrobials (e.g., bacitracin for prevention of necrotic enteritis) may alter the population of antimicrobial-resistant strains in the gut flora (Agunos et al, 2020) interfering with the succession of the microbial population from resistant toward a more susceptible population.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the five lineages typed as OXY-5 in the current study were related to lineages recovered from isolates of K. oxytoca with human origin. The discrimination of the sources of these lineages indicated the widespread of such resistance gene across continents, in different species of either bacteria and/or animals and human being, this's attributed to the global trading of different types of food animals either as frozen meat or as processed food products [47], in addition to, the close contact between human and animals without commitment to perfect infection control rules, permitting the transmission of the carrier bacteria from and to human and the exchange of the resistance genes inbetween different bacterial species.…”
Section: Discussionmentioning
confidence: 99%